Factors Associated With Completion: Pathways Through Developmental Mathematics. (May 2022) - Howell, Elizabeth; Walkington, Candace
This study examines two 5-year longitudinal data sets of community college students ( n = 595 and n = 593) to explore factors associated with successful outcomes in developmental mathematics. Logistic regression models consider the role of demographic factors, course format, and student support structures on the likelihood of a student completing the developmental sequence and subsequently passing a credit-level mathematics course. Additional linear regression models examine the time required to complete developmental coursework. Tutoring has a strong association with positive student outcomes, as does full-time enrollment and developmental mathematics coursework grades. Alternative course formats are also associated with increased likelihood of success for students, but some alternative formats delay a student's time line. Implications for developmental mathematics programs in community college settings are discussed.